The role of nutrition on the treatment of Covid 19 - Samer Younes (Human Nutrition & Metabolism, 2024)
The rapid and extensive transmission of the SARS-CoV-2 virus has led to a worldwide COVID-19 pandemic. Initially thought to be an acute illness, many patients have reported persistent and recurring symptoms even after the infectious period. This has given rise to a new epidemic known as ''long-COVID'' or post-acute sequelae of coronavirus disease, which has significantly impacted the lives of millions of individuals globally. The symptoms of both COVID-19 vary from person to person, but they share similarities with other respiratory viruses, such as chest pain, shortness of breath, and fatigue, as well as adverse effects on metabolic and pulmonary health. Nutrition plays a crucial role in immune function and metabolic health, and therefore, it is believed to have an impact on reducing the risk or severity of symptoms for both COVID-19. However, despite the importance of nutrition in these physiological functions related to COVID-19, the exact role of nutrition in the onset or severity of COVID-19 infection is still not fully understood. This review aims to explore established and emerging nutrition approaches that may have a role in COVID-19, while emphasizing the significance of established nutrition and clinical practice guidelines as the primary resources for patients and healthcare practitioners.